Pressuposição: da sentença ao texto - Oliveira, Iracelane Ferreira da Silva (2014)
This work aims to present a dynamic analysis of presupposition in journalistic news, to point how the presupposed information is altered and how it contributes to the textual development. The study of presupposition is justified by the important discursive role that this linguistic phenomenon performs: it works as an element of cohesion and coherence it prevents the repetition, promotes the semantic recurrence, and establishes the condition of progression. Presupposition is an implicit information linguistically marked by expressions, presupposition triggers, that can be present in simple periods and can be, or not, projected to complex periods. In a dynamic approach, we can consider presupposition beyond the limit of the period, and see it in the textual whole, observing the relevance of the permanence, cancellation or change of the presupposed information. It is important to show that, in some cases, presuppositions are pieces of information that can only be understood clearly by considering the situational context in which they are produced. Our analysis follows a dynamic approach and the corpus is constituted by texts from the newspapers Folha de São Paulo and UOL Notícias. The option for this kind of text was made due to the intention to show the phenomenon of the presupposition in real use situations, and the news, an example of contemporaneous verbal communication with wide social presence, is also a case of a genre in use. The analysis points to the presence of important initial presuppositions, which can be kept in some cases, and cancelled in others, and shows how presuppositional dynamic contributes to the construction of the text.